Remyelination of optic nerve lesions: spatial and temporal factors - Klistorner, Alexandr; Arvind, Hemamalini; Garrick, Raymond; Yiannikas, Con; Paine, Mark; Graham, Stuart L (Multiple sclerosis, 2010)
Optic neuritis provides an in vivo model to study demyelination. The effects of myelin loss and recovery can be measured by the latency of the multifocal visual evoked potentials. We investigated whether the extent of initial inflammatory demyelination in optic neuritis correlates with the remyelinating capacity of the optic nerve. Forty subjects with acute unilateral optic neuritis and good visual recovery underwent multifocal visual evoked potentials testing at 1, 3, 6 and 12 months. Average latency changes were analyzed. Extensive latency delay at baseline significantly improved over time with rate of recovery slowed down after 6 months. Magnitude of latency recovery was independent of initial latency delay. Latency recovery ranged from 7 to 17 ms across the whole patient cohort (average = 11.3 (3.1) ms) despite the fact that in a number of cases the baseline latency delay was more than 35—40 ms. Optic nerve lesions tend to remyelinate at a particular rate irrespective of the size of the initial demyelinated zone with smaller lesions accomplishing recovery more completely. The extent of the initial inflammatory demyelination is probably the single most important factor determining completeness of remyelination. The time period favorable to remyelination is likely to be within the first 6 months after the attack.